Kajian Teologis Gereja Yang Kelihatan dan Tidak Kelihatan - Surimawati Laia; Abad Jaya Zega (Jurnal Filsafat dan Teologi Katolik, 2025)
This study explores the concepts of the visible and invisible Church using a qualitative approach with theological and historical methods. The invisible Church is understood as the true spiritual fellowship of all believers, known only to God, while the visible Church refers to the tangible institution that includes buildings, congregations, organizational structure, and leadership. Throughout Christian history, perspectives on the nature of the Church have varied—some emphasize its spiritual and universal aspects, while others focus on its organizational and institutional dimensions. Through the analysis of biblical passages such as Ephesians 1:22–23 and Colossians 1:18, along with theological insights and historical development, this study finds that a proper understanding of the Church must encompass both dimensions. Misinterpretation between these two concepts can lead to a limited understanding of the Church. The study affirms that the Church is not confined to formal institutions but is also the body of Christ comprising all true believers worldwide. By understanding the balance between the visible and invisible Church, Christians are encouraged to live in unity, strengthen their faith, and take an active and responsible role within church life. This understanding offers a broader perspective for living a more holistic and impactful faith life.